Going for it on Fourth Down: Rivalry Increases Risk Taking, Physiological Arousal, and Promotion Focus - To, Christopher; Kilduff, Gavin J.; Ordoñez, Lisa; Schweitzer, Maurice E. (Academy of Management Journal, 2018)
Risk taking is fundamental to organizational decision making. Extending prior work that has identified individual and situational antecedents of risk taking, we explore a significant relational antecedent: rivalry. In both a field setting and a laboratory experiment, we explore how a competitor’s identity and relationship with the decision maker influences risk taking. We analyze play-by-play archival data from the National Football League and find that interactions with rival (versus nonrival) partners increases risky behavior. In a laboratory experiment involving face-to-face competition, we demonstrate that rivalry increases risk taking via two pathways: increased promotion focus and physiological arousal. These findings highlight the importance of incorporating relational characteristics to understand risk taking. Our findings also advance our understanding of when and why competition promotes risk taking, and underscore the importance of identity and relationships in the psychology and physiology of competitive decision making in organizations.